2020
DOI: 10.1111/iju.14276
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of prostate‐specific antigen testing in men aged ≥55 years: A cross‐sectional study based on patient‐reported outcomes

Abstract: Objectives To examine the predictors of prostate‐specific antigen discussion with a physician and prostate‐specific antigen testing in men aged ≥55 years. Methods Utilizing the USA Health Information National Trends Survey, 4th Ed., a cross‐sectional study from 2011 to 2014 was carried out to analyze the factors predicting prostate‐specific antigen testing and discussion in men ≥55 years. Associations between each covariate and prostate‐specific antigen discussion/testing were determined. Multivariable logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…These findings are in line with previous data demonstrating that cancer prevalence increases with age 19 and that marital status is strongly associated with increased screening for prostate and colon cancers. [20][21][22] Previous studies have shown that gay or lesbian orientation is associated with higher rates of colonoscopies, but it is currently unclear whether sexual orientation impacts PSA testing. [23][24][25][26][27] In contrast, a lower probability of undergoing both screening tests was associated with AIAN and Asian race (vs White) and current smokers (vs never-smokers).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with previous data demonstrating that cancer prevalence increases with age 19 and that marital status is strongly associated with increased screening for prostate and colon cancers. [20][21][22] Previous studies have shown that gay or lesbian orientation is associated with higher rates of colonoscopies, but it is currently unclear whether sexual orientation impacts PSA testing. [23][24][25][26][27] In contrast, a lower probability of undergoing both screening tests was associated with AIAN and Asian race (vs White) and current smokers (vs never-smokers).…”
Section: Discussionmentioning
confidence: 99%